2015
DOI: 10.1371/journal.pone.0119751
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Human Polarized Macrophages: More than One Role of Alternative Activation?

Abstract: BackgroundMacrophages are a heterogeneous cell population which in response to the cytokine milieu polarize in either classically activated macrophages (M1) or alternatively activated macrophages (M2). This plasticity makes macrophages essential in regulating inflammation, immune response and tissue remodeling and a novel therapeutic target in inflammatory diseases such as atherosclerosis. The aim of the study was to describe the transcriptomic profiles of differently polarized human macrophages to generate ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 56 publications
6
62
0
3
Order By: Relevance
“…M1 polarization of macrophages was associated with the most dramatic changes in gene expression, whereas nonpolarized M0 and M2a- and M2c-polarized macrophages revealed subtle genetic differences and possessed more closely aligned expression patterns, consistent with prior reports of microarray analyses (36, 37). Among the genes that most clearly distinguished M1 macrophages were the transcription factors IRF1 and STAT1 ; the receptors CCR7 , CD80 , IL15RA , and MET ; a variety of cytokines, such as CXCL9 , CXCL10 , and CXCL11 ; the enzyme PTGS2 ; the Ca channel KCNN2 ; and the lncRNAs CCDC26 and RP11-419k12.1 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…M1 polarization of macrophages was associated with the most dramatic changes in gene expression, whereas nonpolarized M0 and M2a- and M2c-polarized macrophages revealed subtle genetic differences and possessed more closely aligned expression patterns, consistent with prior reports of microarray analyses (36, 37). Among the genes that most clearly distinguished M1 macrophages were the transcription factors IRF1 and STAT1 ; the receptors CCR7 , CD80 , IL15RA , and MET ; a variety of cytokines, such as CXCL9 , CXCL10 , and CXCL11 ; the enzyme PTGS2 ; the Ca channel KCNN2 ; and the lncRNAs CCDC26 and RP11-419k12.1 .…”
Section: Resultssupporting
confidence: 87%
“…We also make the observation that oxidative phosphorylation is upregulated in glioblastoma blood monocytes relative to normal donors. Oxidative phosphorylation has been previously associated with the M0 and M2 phenotypes (37, 50) in contrast to glycolysis utilization in M1 cells. Whether these changes in the metabolic phenotype can occur in the circulation has been previously debated (51) with the presumption being that this occurs only at the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages highly express IL-12, IL-23, major histocompatibility complex (MHC) and B7 family members. The main function of M1 macrophages includes the promotion of antigen presentation and Th1 activation [9]. M1 macrophages can secrete proinflammatory cytokines and immune activation factors to promote inflammation and antitumor function [8].…”
Section: The Origin and Differentiation Of Macrophagesmentioning
confidence: 99%
“…While Williams et al (2002) found that just 19 genes were upregulated in M2c macrophages after 3 h of IL-10 stimulation, Derlindati et al (2015) reported that no genes were upregulated after 6, 12, and 24 h of polarization. Therefore, the purpose of this study was to identify a gene expression signature for M2c macrophages using whole transcriptome shotgun sequencing, or RNA-seq, a more sensitive method of gene expression analysis.…”
Section: Introductionmentioning
confidence: 99%